The Causes and Conditions of Child Violence: The Rapes Case - Bulgamaa, Rinzaan (Advances in Social Sciences Research Journal, 2025)
The main purpose is to investigate the increased frequency of rape and indecent assault against kids, despite strengthened legal restrictions and prevention efforts. It seeks to identify and examine the primary contributing factors—such as family instability, inappropriate relationships, household drunkenness, unsupervised internet usage, and insufficient child supervision—that put children, particularly those aged 8 to 17, at danger. The study aims to evaluate the efficacy of current preventative and protection initiatives, emphasizing the need for enhanced implementation, professional ability, and social commitment to protecting children’s rights. Finally, it aims to inform more effective, evidence-based approaches for reducing and preventing sexual assault against children. The number of rapes and indecent attacks on kids has risen annually, with an average of 320 incidents reported each year, however a little decline is expected in 2024. Despite improved legal restrictions and NGOs’ efforts, the incidence of child rape continues to rise by 14.2-22.8 percent each year, with many cases buried behind birth and abortion statistics. Key contributing variables include family instability, improper interactions, household drinking, unsupervised internet use, and insufficient kid supervision, with the majority of victims aged 8-17 and perpetrators being adults with lower educational attainment. Effective prevention and response necessitate not only strong laws, but also coordinated implementation, professional ability, and a social commitment to protecting children’s rights and safety.